ПЕДАГОГІЧНА СПРЯМОВАНІСТЬ ОСОБИСТОСТІ ЯК ОСНОВА ФОРМУВАННЯ ПЕДАГОГІЧНОЇ КУЛЬТУРИ МАЙБУТНЬОГО ВЧИТЕЛЯ (Педагогіка вищої та середньої школи, 2003)
In the article, the pedagogical trend comes out as the subject of exploration by many investigators. The author argues the necessity of scientific basis and organized the plan with the purpose of exposing and training the student's pedagogical trends as the foundation of forming future teachers' pedagogical traditions.